War at the Snow White Motel and others stories - Wynne-Jones, Tim (Groundwood Books/House of Anansi Press, 2020)
Presents a collection of nine children's stories featuring pivotal moments in life. In the titular "War at the Snow White Motel," young Rex, with his family on vacation in Vermont, makes an enemy with a much bigger and older teenager at their motel--but the Vietnam War looms large in the background.